Trends of acetaminophen overuse among ambulatory patients in Lebanon - Ramadan, Wijdan H. (2016)
Acetaminophen (APAP), also known as paracetamol, is used by millions of people worldwide for its antipyretic and analgesic properties. At therapeutic doses, APAP is effective and safe. However, the long-term use and the ingestion of inappropriately high doses pose substantial risks to APAP users. APAP has been the leading cause of acute liver injury across the globe. No studies previously assessed APAP usage patterns in Lebanon, the objective of the study is to evaluate the appropriateness of APAP use among the community pharmacy patients across Lebanon as a first step to understand and postulate safety recommendation. A cross-sectional survey was performed in 45 pharmacies randomly selected across Lebanon. A 17-item questionnaire was used to record patterns of APAP use among the Lebanese adult population.2160 participants were found taking APAP or APAP containing products with a mean age of mean 40.83±16.36. The prevalence of acetaminophen use as single ingredient was 46.8%, while 53.2% were using APAP combination products. One in ten participants ingested a total daily dose of more than the recommended 4 g. Half of APAP users reported taking the drug daily for “as long as they needed it” before consulting a healthcare professional. Heavy alcohol intake was reported by 30.4% of the users and 8% of the users suffered from liver disease. The study identified APAP over users among a significant percentage of community pharmacy patients in Lebanon. It is essential to raise awareness among patients on the appropriate use of APAP as well as the compelling risks of concomitant chronic ingestion of alcohol and other hepatically metabolized substances.